Seasonal dynamics of carp infection with Bothriocephalus sp. in cage farming under the new conditions - D. P. Skachkov; Yu. A. Puhovski; V. T. Orlov (Российский паразитологический журнал, 2019)
The purpose of the research: is studying the seasonal dynamics of carp infection with Bothriocephalus sp. in cage farming under the new conditions (no discharge into the reservoir-cooler of warm water, wintering in cages under the ice). Materials and methods. To study the dynamics of contamination of carp yearlings with Bothriocephalus sp. In JSC Cherepetskaya fish farm is chosen 4 cage with fingerlings of carp. Monthly, from April to November 2017, the helminthological autopsy carried out on 10 yearlings carp from each tank to establish the extensiveness and intensity of infection of fish with Bothriocephalus sp. The content of soluble oxygen in water and measured the water temperature in the zone of location of the garden lines determined daily. After carrying out preventive treatments with microsal fish from all experimental cages were opened and the effectiveness of treatment was determined. Results and discussion. Carp are infected with Bothriocephalus sp. in April at 30-50%, in May there was a slight increase of the infection (40- 50%). After the first treatment with feed drug mixtures with microsal, a significant decrease in the infection of the fish with Bothriocephalus sp. occurred. In three cages 100% efficiency was obtained. In the cage No 21, the effectiveness of treatment was 75,0%. In June 2017, in the No. 21 cage, fish contamination increased till 20%. In the remaining three experimental cages, the fish did not infected. At the end of July, there was a sharp increase in the extensiveness and intensity of infection of fish by Bothriocephalus sp. - from 10 to 40% at an invasive rate from 1 to 2,25 cestodes per fish. In August, the extent of infection continued to grow and amounted to 30-60% for different experimental cages, the intensity of infection remained at the same level. On September 18, 2017, after the second treatment of fish with the therapeutic granulated mixed fodder with microsal, efficiency in cages No 5, No. 25 and No 36 was 100%. In the cage No 21, efficiency was 83,3%. In October and November 2017 there was an insignificant increase in fish infection by cestodes. The incidence of infection in October was 10% in the cage No 21, 20% and 10% in the cages 21 and 36 respectively. In the remaining experimental cages, the infection of fish with Bothriocephalus sp. is not established.